The Effect of Merit System Career Development on Employee Performance through Transparency of Career Development in the State Apparatus of Mojokerto Regency - Haryadi, M. Sukron; Dyah Sawitri; Dwi Orbaningsih (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Developing professional and integrity-driven human resources (HR) is key to improving the quality of public services in Indonesia. In this context, career development for civil servants based on a merit system is important to consider, particularly regarding transparency. This study aims to analyze the influence of merit-based career development on transparency and employee performance within the Civil Service (ASN) of Mojokerto Regency. The method used is quantitative with an explanatory research approach, involving 87 employees who experienced transfers and promotions. Data was collected through questionnaires and analyzed using SPSS statistical software. The findings indicate that merit-based career development significantly influences the transparency of the career development system and employee performance, with transparency acting as a mediating variable. The t-test results show that merit-based career development significantly influences employee performance, and transparency in career development increases motivation and job satisfaction. The conclusion of this study emphasizes that transparent and fair career development policies can improve overall employee performance. Therefore, it is recommended that policymakers in Mojokerto Regency design and implement more transparent policies in the career development process and conduct regular evaluations to ensure that employee needs are met and organizational performance can continue to be improved. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 16: Peace, Justice, and Strong Institutions